Prenatal Exposure to Secondhand Smoke and the Development of Self-Control - Meldrum, Ryan Charles (Journal of developmental and life-course criminology, 2017)
The purpose of this study was to evaluate whether prenatal exposure to secondhand smoke among non-smoking mothers is associated with their child’s development of self-control from childhood into adolescence.